Organization of the fight against COVID-19 in a hospital institution. Cienfuegos Province, 2020-2021 - Vivian Isabel Chávez Pérez; Helvia Manuela Reyes Cabrera; Hilda María Delgado Acosta; Lourdes Elena Duany Badell (Medisur)
Background: epidemics of unknown emerging diseases test not only the technical and human capacity of health professionals, but also of all those who make up the scientific community in society. Objective: to describe the organization of health care services in the fight against COVID-19 at the Héroes de Paya Girón Specialized Outpatient Center, in Cienfuegos. Methods: a research was carried out on health systems and services that describe the stages of hospital reconversion for the care of suspected and confirmed patients, the number of admitted patients, the extension to a nearby school center and the maintenance of other vital services. Human resources and availability of beds for patient care were also taken into account. The After Action Review method was applied to study lessons learned. The information was obtained from interviews with ten key informants and from the statistics and human resources departments’ reports. Results: the organization of medical care during the year 2020 was related to the evolution of the pandemic in the province. 569 adults and 91 pediatric patients were admitted. On January the 5th, 2021, the second stage of confronting the disease began and the mission of the center was transformed towards the care of positive cases of COVID-19, the number of intensive care beds was increased, a sign of the progressive worsening of patients especially from the end of June, July and August 2021. Conclusions: it can be affirmed that there is a center in the Cienfuegos Province with the capacity to rearrange itself in less than 24 hours to take care of patients with emerging infectious diseases. This shows the need to increase the training of Graduates in Intensive Nursing, as well as to create an Organization and Procedures Manual in each service, adjusted to the care protocols and asepsis, antisepsis and biosafety measures.